2014
DOI: 10.1530/rep-13-0191
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated AKT preserves stallion sperm viability and motility by inhibiting caspases 3 and 7

Abstract: AKT, also referred to as protein kinase B (PKB or RAC), plays a critical role in controlling cell survival and apoptosis. To gain insights into the mechanisms regulating sperm survival after ejaculation, the role of AKT was investigated in stallion spermatozoa using a specific inhibitor and a phosphoflow approach. Stallion spermatozoa were washed and incubated in Biggers-Whitten-Whittingham medium, supplemented with 1% polyvinyl alcohol (PVA) in the presence of 0 (vehicle), 10, 20 or 30 mM SH5, an AKT inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 57 publications
(55 reference statements)
3
71
0
Order By: Relevance
“…Recently it was suggested that phosphorylated Akt maintains the membrane integrity of ejaculated stallion spermatozoa, presumably by inhibiting caspases 3 and 7, which preserves sperm vitality (34). Here we report for the first time a negative correlation between phosphorylated Akt (pT308) levels and the percentage SDF, which supports a role of Akt in sperm survival.…”
Section: Discussionsupporting
confidence: 78%
“…Recently it was suggested that phosphorylated Akt maintains the membrane integrity of ejaculated stallion spermatozoa, presumably by inhibiting caspases 3 and 7, which preserves sperm vitality (34). Here we report for the first time a negative correlation between phosphorylated Akt (pT308) levels and the percentage SDF, which supports a role of Akt in sperm survival.…”
Section: Discussionsupporting
confidence: 78%
“…Detection of more subtle changes in the sperm membrane requires the use of other probes. Fluidity of sperm membranes can be assessed with merocyanine 540 [24], and subtle increases in the permeability of the sperm plasma membrane can be detected with YoPro-1 [25,26]. Yo-Pro-1 is routinely used in the authors' laboratory in combination with PI; H33342 is also incorporated to sort debris.…”
Section: The Sperm Membrane: Integrity Permeability Fluidity and Fmentioning
confidence: 99%
“…Recently, mitotracker dyes [35,36] have become available in multiple colors and provide colorful alternatives to be used in multicolor experiments. Both JC-1 and Mitotracker deep red have been recently used in our laboratory [25]. These probes measure different aspects of mitochondrial function; JC-1 reflects mitochondrial membrane potential, while mitotracker deep red passively diffuses across membranes and binds to thiols in active mitochondria.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly also new data on the heterogeneity of the individual sperm cells or of sperm cell subpopulations within a sample will be available. Toward this end, it may be useful the use of flow cytometry sorting of the different cells based on specific modifications [105].…”
Section: Five-year Viewmentioning
confidence: 99%